DNA Repair Gene Polymorphisms in Non-Small-Cell Lung Cancer Patients Treated with First-Line Platinum-Containing Chemotherapy. Issue 4 (July 2016) - Rulli, Eliana; Marabese, Mirko; Piva, Sheila; Bonomi, Lucia; Caiola, Elisa; Ganzinelli, Monica
Purpose: Single nucleotide polymorphisms (SNPs) in the DNA repair genes are believed to contribute to the clinical outcome of patients receiving platinum-based chemotherapy. We investigated the impact of 2 SNPs of excision repair cross-complementation group 1 and 2 of xeroderma pigmentosum complementation group G on the outcome in patients with non-small-cell lung cancer (NSCLC) treated with platinum-based chemotherapy. Methods: Between October 2007 and March 2012, we collected 374 blood samples from consecutive patients registered in the TAILOR trial. Four SNPs (rs11615, rs3212986, rs17655, rs1047768) were genotyped using real-time polymerase chain reaction. Results: The rs11615 polymorphism was associated with histotype (p = 0.0123). No other correlations were found with clinical variables or with EGFR or KRAS mutational status. None of the SNPs had any impact on overall survival or progression-free survival. Conclusions: The findings suggest that the investigated SNPs do not make any significant contribution to the outcome of NSCLC.